The impact of HIV on hepatocellular cancer survival in Nigeria. Issue 3 (20th December 2020) - Okeke, E.; Mark Davwar, P.; Mullen, B.; Duguru, M.; Agbaji, O.; Sagay, A.; Murphy, R.; Hawkins, C.
Abstract: Background: Hepatocellular carcinoma (HCC) is an increasing cause of mortality in HIV‐infected individuals. We compared host and tumour characteristics between HIV‐infected and HIV‐uninfected Nigerians with HCC and examined the impact of HIV on survival. Methods: This prospective observational study was conducted at Jos University Teaching Hospital in Jos, Nigeria, among adults (>18 years) with HCC enrolled between September 2015 and September 2017 and followed until April 2019. Demographics, tumour characteristics and survival were compared between HCC subjects with and without HIV. Results: 101 (10 HIV‐infected and 91 HIV‐uninfected) subjects were enrolled [male 72%; median age 48 (IQR 35–60)]. 60% HIV‐infected subjects were receiving ART; 90% had CD4 counts ≥ 200/mm 3 at HCC diagnosis, and 20% had HIV RNA levels < 20 copies/mL. 57.4% were infected with chronic HBV (HBsAg+). The duration of symptoms was shorter in HIV‐infected vs . HIV‐uninfected subjects [93 (IQR 54–132) vs . 155 (93–248] days; p = 0.02]. At the end of follow‐up, 99 of 101 (98.0%) subjects were confirmed to have died: 9 of 10 (90.0%) HIV‐infected and 90 of 91 (98.9%) HIV‐uninfected. The probability of survival at three months was 22% and 47% in HIV‐infected and HIV‐uninfected subjects, respectively ( P = 0.02). Median time to death was significantly shorter in HIV‐infected vs . HIV‐uninfected subjects [24 days (IQR 16–88) vs . 85 days (IQR 34–178), respectively ( P = 0.03)]. Conclusions: High early mortality was observed in this cohort of Nigerian adults with HCC. HIV infection was associated with a faster clinical presentation and shorter survival. More aggressive HCC surveillance may be warranted in HIV‐infected subjects, particularly if they are co‐infected with chronic HBV. Abstract : Contexte: Le carcinome hépatocellulaire (CHC) est une cause croissante de mortalité chez les personnes infectées par le VIH. Nous avons comparé les caractéristiques de l'hôte et de la tumeur entre les Nigérians avec le CHC infectés par le VIH et non infectés et avons examiné l'impact du VIH sur la survie. Méthodes: Cette étude observationnelle prospective a été menée au Jos University Teaching Hospital à Jos, au Nigéria, chez des adultes (>18 ans) avec CHC inscrits entre septembre 2015 et septembre 2017 et suivis jusqu'en avril 2019. Les données démographiques, les caractéristiques tumorales et la survie ont été comparées entre les sujets CHC avec et sans VIH. Résultats: 101 sujets (10 infectés par le VIH et 91 non infectés par le VIH) ont été recrutés [hommes 72%; âge médian de 48 ans (IQR 35‐60)]. 60% des sujets infectés par le VIH recevaient une ART; 90% avaient des taux de CD4 ≥200/mm 3 au moment du diagnostic de CHC et 20% avaient des taux d'ARN du VIH <20 copies/ml. 57, 4% étaient chroniquement infectés par le VHB (HBsAg +). La durée des symptômes était plus courte chez les sujets infectés par le VIH que ceux non infectés [93 (IQR 54‐132) vs 155 (93‐248] jours; p = 0, 02]. A la fin du suivi, 99/101 (98, 0 %) des sujets ont été confirmés décédés: 9/10 (90, 0%) sujets infectés par le VIH et 90/91 (98, 9%) non infectés par le VIH. La probabilité de survie à trois mois était de 22% et 47% chez les personnes infectées par le VIH et celles non infectées par le VIH, respectivement ( p = 0, 02). Le délai médian au décès était significativement plus court chez les sujets infectés par le VIH par rapport aux sujets non infectés par le VIH [24 jours (IQR 16‐88) contre 85 jours (IQR 34‐178), respectivement ( p = 0, 03)]. Conclusions: Une mortalité précoce élevée a été observée dans cette cohorte d'adultes nigérians atteints de CHC. L'infection par le VIH était associée à une présentation clinique plus rapide et à une survie plus courte. Une surveillance plus étroite du CHC peut être justifiée chez les sujets infectés par le VIH, particulièrement s'ils sont coinfectés chroniquement par le VHB.